2018
DOI: 10.26817/16925777.433
|View full text |Cite
|
Sign up to set email alerts
|

Graphic Organizers Support Young L2 Writers’ Argumentative Skills

Abstract: Learners are increasingly required to analyze critically information presented in languages other than their first to form reasoned opinions and solve problems. It is thus urgent to develop their argumentation skills, needed not only for academic success but also later professional life—and, indeed, by participant citizens in democratic societies. Although there has been some increased interest in teaching argumentation at pre-tertiary levels, this remains a relatively unexplored issue in Colombia (and, indeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…The finding that graphic organizers (GOs) differ significantly from non-graphic organizers (NGOs) on writing performance is in accordance with earlier studies that found GOs to be an effective strategy to improve writing skills (Ningrum & Crosthwaite, 2020;Rahmat, 2020;Setyowati, Sukmawan, & El-Sulukiyyah, 2020;Anderson et al, 2018;Anggraeni & Pentury, 2018;Maharani, 2018;Wahyuni & Umam, 2017;Vitanofa & Anwar, 2017;Setyowati, Sukmawan, & Nurmansyah, 2017;Jumariati & Sulistyo, 2017;Khalaji, 2016;Aunurrahman, Hamied, & Emilia, 2016;Khatib & Meihami, 2015;Mustafa & Samad, 2015;Meera & Aiswary, 2014;Robinson & Kiewra, 1995). The study evidence that GOs can be used successfully in L2 argumentative writing classes.…”
Section: Discussionsupporting
confidence: 90%
“…The finding that graphic organizers (GOs) differ significantly from non-graphic organizers (NGOs) on writing performance is in accordance with earlier studies that found GOs to be an effective strategy to improve writing skills (Ningrum & Crosthwaite, 2020;Rahmat, 2020;Setyowati, Sukmawan, & El-Sulukiyyah, 2020;Anderson et al, 2018;Anggraeni & Pentury, 2018;Maharani, 2018;Wahyuni & Umam, 2017;Vitanofa & Anwar, 2017;Setyowati, Sukmawan, & Nurmansyah, 2017;Jumariati & Sulistyo, 2017;Khalaji, 2016;Aunurrahman, Hamied, & Emilia, 2016;Khatib & Meihami, 2015;Mustafa & Samad, 2015;Meera & Aiswary, 2014;Robinson & Kiewra, 1995). The study evidence that GOs can be used successfully in L2 argumentative writing classes.…”
Section: Discussionsupporting
confidence: 90%
“…When learners are provided with authentic sources of input, content is usually supported through graphic organisers to orient learners towards key concepts and terms (e.g. Anderson, Mora González, & Cuesta Medina, 2018).…”
Section: Research With Successful Resultsmentioning
confidence: 99%
“…One of the geographical contexts in which CLIL has disembarked is South America. According to a review of CLIL in South America between 2008and 2018, 2008 could be considered the year which witnessed the first outputs (e.g., Fernández, 2008) drawing on CLIL practices in the region. Since then, regional and, to a significant lesser extent, international outlets have included empirical and descriptive articles of CLIL in practice conducted in South America.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive theory states that students can organize and link information in a structured way to make it easier to work on or answer questions (Davoudi & Yousefi, 2014;Tayib, 2015). Meanwhile, constructivism theory relates to students' ability to create concepts or ideas and express their own opinions on their essays (Cheng & Gwo, 2019; Fadhil & Yamal, 2020; Mochizuki et al, 2019;Anderson et al, 2018;Ponce et al, 2013;Wei, 2019;Younis, 2019). Cognitive Load Theory, on the other hand, signifies that graphic organizers can lighten students' excessive cognitive load when combining ideas in their writing that are tailored to the purpose of the writing (Lee & Tan, 2010).…”
Section: Title…… Figure 2 Generic Structure Of Opinion Essaymentioning
confidence: 99%
“…By writing, people can convince readers by conveying their ideas or opinions that are supported by relevant facts or events presented logically (Setyowati, 2016). For teachers, teaching the content and knowledge of language skills is highly essential in teaching a second or foreign language (Anderson et al, 2018). This includes writing, which is a very challenging language skill to teach in foreign language classes since it requires attention to the macro and micro parts of writing as well as the structure (Oshima & Hogue, 2007;Regan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%